The Relationship Between Empathy and Stringency of Punishment in Mock Jurors - Mattias Per Sjöberg (Journal of European Psychology Students, 2015)
The aim of the present study is to investigate the relationship between empathy and stringency of punishment in mock jurors. 291 law and non-law students (123 male, 166 female) participated in the study. Participants first read a court case explaining that the defendant was found guilty of aggravated assault. Participants then made a sentencing decision for the defendant and later answered the Interpersonal Reactivity Index (IRI). The results revealed a significant negative correlation between overall empathy and stringency of punishment. Two of the four sub-scales of the IRI (perspective taking and empathic concern) were of interest in the current study, and as hypothesized each showed a significant negative correlation with stringency of punishment.